2013
DOI: 10.1126/science.1229223
|View full text |Cite
|
Sign up to set email alerts
|

Probing Allostery Through DNA

Abstract: Allostery is well documented for proteins but less recognized for DNA-protein interactions. Here we report that specific binding of a protein on DNA is substantially stabilized or destabilized by another protein bound nearby. The ternary complex's free energy oscillates as a function of the separation between the two proteins with a periodicity of ~10 base pairs, the helical pitch of B-form DNA, and a decay length of ~15 base pairs. The binding affinity of a protein near a DNA hairpin is similarly dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
278
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(319 citation statements)
references
References 70 publications
36
278
5
Order By: Relevance
“…Allosteric modulation of DNA may provide one explanation for this observation. Transcription factors such as glucocorticoid receptor were recently reported to modulate DNA allosterically to facilitate binding by another DNAbinding protein that does not appear to make protein-protein contacts (52). Furthermore, we have previously shown that a polyamide, lacking a domain to interact with a protein partner, facilitates the binding of a transcription factor to an adjacent site by 10-fold (53).…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric modulation of DNA may provide one explanation for this observation. Transcription factors such as glucocorticoid receptor were recently reported to modulate DNA allosterically to facilitate binding by another DNAbinding protein that does not appear to make protein-protein contacts (52). Furthermore, we have previously shown that a polyamide, lacking a domain to interact with a protein partner, facilitates the binding of a transcription factor to an adjacent site by 10-fold (53).…”
Section: Discussionmentioning
confidence: 99%
“…This is typically the case when the DNA deformation anticipates the DNA structure in the complex formed by the binding site and its ligand. And pertinent to eukaryotic gene expression, closely positioned nucleosomes have been shown quite recently to modify the binding affinity of a transcription factor to a response element inserted in a neighboring linker DNA [31]. Note that speaking of DNA deformation implicitly refers to a lock-and-key mechanism, which may not be the case: an alternative view is a shift of an equilibrium between two pre-existing DNA conformations upon the first binding event (conformational capture).…”
Section: Protein-binding Event May Trigger Dna Allosteric Transitionsmentioning
confidence: 99%
“…The impact of DNA polymorphism in DNA allosterism [64] has been also the subject of the work of several groups [62,65], while others centered their efforts in understanding the origin of DNA curvature [66]. Minicircles, a specially curved form of DNA traditionally challenging for the field due to the high mechanical tension that they can incorporate, have been recently revisited by different authors who explored the origins of superhelicity and the limits of the elastic response of DNA to distortion [66,67].…”
Section: Atomistic Studiesmentioning
confidence: 99%